دراسة تقييمية للمؤشرات التنموية والإحصائية الخاصة بتحقيق أهداف الألفية الإنمائية في سورية: - محمود محمد إبراهيم; الخيّر شادي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث موضوع أهداف الألفية الإنمائية الخاصة بالأمم المتحدة و دراسة مدى تحقيقها في الجمهورية العربية السورية من خلال استعراض عدد من المؤشرات التنموية و البيانات الإحصائية المتعلقة بها. حيث يقوم البحث في البداية بالتعريف بأهداف الألفية الإنمائية و استعراض الأهداف الرئيسية الثمانية والفرعية الثمانية عشرة الخاصة بها والتعريف بالمؤشرات الإحصائية الخاصة بقياس مدى تحقق هذه الأهداف. من ثم ينتقل البحث إلى التركيز على دراسة مدى تحقيق أهداف الألفية في سورية من خلال مقارنة وتحليل عدد من المؤشرات التنموية والإحصائية الخاصة بها واستعراض أهم الجهود الوطنية في مجال العمل على تحقيق هذه الأهداف وبناء التنمية الاقتصادية والاجتماعية. وختم البحث باستعراض النتائج التي تم التوصل إليها إضافة إلى عرض بعض المقترحات الخاصة بتطوير وتعزيز العمل على تحقيق أهداف الألفية و بناء التنمية المستدامة في سورية. أخيراً يستعرض البحث عدد من الجداول الإحصائية الخاصة ببعض المؤشرات الإحصائية لأهداف الألفية في سورية مقارنة ببيانات من بسنوات سابقة. This research focuses on the United Nation’s Millennium Development Goals and studies the achievement of these goals in Syrian Arab Republic throughout a number of development indicators and statistical data that are involved with these goals. At first, this research defines the Millennium Development Goals and its eight primary and eighteen secondary targets, and the definition of its statistical indicators, which measure the achievement of these goals. After that the research continues to focus on studying and measuring the achievement of these Millennium Goals in Syria by comparing and analyzing a number of its development and statistical indicators, and it evaluates the national efforts in the field of working toward achieving these goals and building a social economic development in Syria. In conclusion, the research demonstrates the results of this study and proposes a number if suggestions involving strengthening the work and effort to achieve these Millennium Goals and build sustainable development in Syria. Finally, the research browses a number of timetables involving some of the statistical indicators of Millennium Development Goals in Syria compared to data from previous years.